Faktor Ekonomi yang Mempengaruhi Minat Konsumen Untuk Menggunakan Sistem Pembangkit Listrik Tenaga Surya (PLTS) Atap di Kota Palembang - Frastuti, Melia; Royda (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
The purpose of this study is to determine whether there is an influence of economic factors that affect people's interest in using the Solar Roofing Power Generation System (PLTS) in Palembang. Data analysis methods used are qualitative and quantitative, with primary and secondary data sources in the form of questionnaires and interviews. The population in this study were all consumers of PT. PLN in the city of Palembang which has power> 2200 VA. Sampling using the Slovin formula obtained as many as 400 respondents, the sampling technique using proportionate stratified random sampling with the location of rayon into sub-populations. The results showed that there was a significant influence between economic factors on people's interest in using the PLTS Roof system with Sig 0,000.